2013
DOI: 10.1111/ene.12176
|View full text |Cite
|
Sign up to set email alerts
|

Reduced α‐synuclein levels in cerebrospinal fluid in Parkinson's disease are unrelated to clinical and imaging measures of disease severity

Abstract: CSF α-synuclein levels are reduced in patients with PD compared with healthy controls. However, sensitivity and specificity indicate that α-synuclein will not suffice as a single biomarker. CSF α-synuclein levels do not correlate with measures of disease severity, including striatal dopaminergic deficit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 26 publications
5
55
1
2
Order By: Relevance
“…CSF total-a-synuclein has ranged in previous studies from non-significant [13][14][15][16] to modest lowering in PD vs. controls [7][8][9][10][11][12]. Even though the lack of differences in CSF total a-synuclein in our study including for the first time iRBD patients might suggest that CSF total a-synuclein is not a premotor or diagnostic PD biomarker, the presence of significant MRI correlates of this CSF marker even in iRBD patients supports further longitudinal research of the combined use of CSF total a-synuclein and quantitative MRI (CTh) as candidate biomarkers of progression of iRBD to PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CSF total-a-synuclein has ranged in previous studies from non-significant [13][14][15][16] to modest lowering in PD vs. controls [7][8][9][10][11][12]. Even though the lack of differences in CSF total a-synuclein in our study including for the first time iRBD patients might suggest that CSF total a-synuclein is not a premotor or diagnostic PD biomarker, the presence of significant MRI correlates of this CSF marker even in iRBD patients supports further longitudinal research of the combined use of CSF total a-synuclein and quantitative MRI (CTh) as candidate biomarkers of progression of iRBD to PD.…”
Section: Discussionmentioning
confidence: 99%
“…CSF total-a-synuclein levels in PD vs. controls have ranged in different studies from significant reductions [7][8][9][10][11][12] to similar levels [13][14][15][16]. Blood contamination of CSF has been pointed as a possible explanation for such discrepancies, but it remains unclear why among positive studies, some have needed controlling for CSF haemoglobin levels to find significant CSF total-a-synuclein reductions in PD [7,11], and some have not [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for the differences in the sensitivity and specificity may be that Mollenhauer and colleagues recruited a cohort that was larger and diagnostically more diverse, including dementia with Lewy bodies (DLB) and MSA, which are atypical Parkinsonian disorders [22]. No correlation between the α-synuclein level and disease severity was found in these two studies, which was later confirmed by another study [24]. The oligomeric form of α-synuclein was increased in CSF of patients with Lewy body disease (PD and DLB combined) compared to non-Lewy body disease subjects (controls and tauopathies).…”
Section: Abnormal Protein Accumulation and Aggregation α-Synucleinmentioning
confidence: 99%
“…Correlated with PD severity [14] [9] α-Synuclein↓ [7,22] 71% sensitivity and 53% specificity patients with PD vs. controls, DLB, and MSA [22] Phosphorylated α-synuclein↑ [21,23] No correlation between the α-synuclein level and PD severity [7,19,22,24] Antibody towards monomeric α-synuclein↑ [25] Tau Total tau↓ [26] Distinguish Patients with low UA levels in serum may be more prone to developing PD, and an inverse relationship between UA and severity of PD was robust for men but weak for women [11]. Another study in the Chinese population reported similar results, which suggests that the serum UA level could be a useful biomarker of PD diagnosis and disease progression [12].…”
Section: ↑[14]mentioning
confidence: 99%
“…71,128,129 In a secondary analysis of the DATATOP study, lower baseline CSF α-syn levels predicted a better preservation of cognitive functions in early PD patients after 8-year-follow-up. 72 Another analysis of the DATATOP study found an association between higher phosphorylated-tau protein and greater decline in cognitive functions but slower motor progression.…”
Section: Csf Biomarkersmentioning
confidence: 99%